REXTRAP and REXEBIS: Monte Carlo Simulation of Ion Recoil Effects in Beta Decay - Ohlsson, Fredrik (My University, 2007)
This thesis describes a Monte Carlo code for simulation of the Beta decay of radioactive isotopes and its influence on the ion dynamics in the REXTRAP and REXEBIS devices at the REX-ISOLDE post-acceleration facility at CERN. It was developed as a project under the CERN Summer Student Program in the summer of 2007. In addition to the charge and mass change caused by the decay, the simulation takes the recoil of the daughter ion, and its effect on the ion dynamics, into account. The object of the simulation is to study the effect of the decay on the REX-ISOLDE beam composition delivered to the post-accelerator and ultimately impacting on the experimental target at the end of the beam line. The theory of Beta decay is briefly reviewed as well as the statistical methods used. The models used for the components of the REXTRAP and REXEBIS are then described in detail together with their implementation in a MATLAB code. Finally, the results produced by the simulation are analyzed and compared to estimates based on simple decay models and on measurements on a 80Zn beam.
Keywords: Kärnfysik; Beräkningsfysik; Nuclear physics; Computational physics